HUMAN RESOURCE MANAGEMENT PRACTICES IN SHIPPING COMPANIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In today's competitive business world, it will be increasingly challenging to meet the needs of businesses and individuals. Strategic human resource management (HRM) strategies have an impact on a company's ability to compete in today's market. Human resource management in shipping enterprises will be examined in this research. Training and performance evaluation, followed by career development, emerged as two of the most important aspects of human resources (HR). Shipping firms used 'Job analysis and HR planning' to a lesser extent than other industries. Workforce diversity and flexibility were also mentioned, but they did not emerge as a noteworthy practice.